2009
DOI: 10.1523/jneurosci.5309-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Cause of the Imbalance in the Neuronal Network Leading to Seizure Activity Can Be Predicted by the Electrographic Pattern of the Seizure Onset

Abstract: This study investigates the temporal dynamics of ictal electrical activity induced by injection of the GABA A receptor antagonist bicuculline, and the glutamate agonist kainic acid, into the CA3 area of hippocampus. Experiments were conducted in freely moving adult Wistar rats implanted with microelectrodes in multiple brain areas. Wide-band electrical activity (0.1-3000 Hz) was recorded, and the latency of seizure onset as well as the pattern of electrical activity were investigated for each drug. The latenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…As in our previous studies involving hippocampal picrotoxin infusions , observations of the rats following infusions and between infusion days, did not reveal infusion-induced motor convulsions or more subtle indicators of seizure development, such as facial twitches, tremor, movement arrest or wet-dog shakes, which may result from higher doses of GABA antagonists (Bragin et al 2009). Furthermore, our electrophysiological studies did not indicate electrophysiological seizure signs (see below).…”
Section: Microinfusions For Behavioural Studiessupporting
confidence: 59%
“…As in our previous studies involving hippocampal picrotoxin infusions , observations of the rats following infusions and between infusion days, did not reveal infusion-induced motor convulsions or more subtle indicators of seizure development, such as facial twitches, tremor, movement arrest or wet-dog shakes, which may result from higher doses of GABA antagonists (Bragin et al 2009). Furthermore, our electrophysiological studies did not indicate electrophysiological seizure signs (see below).…”
Section: Microinfusions For Behavioural Studiessupporting
confidence: 59%
“…3). Excitatory field events similar to PID have been detected just before seizures in animal models 6,8,15,43,44 . PID do not involve barrages of hyperpolarizing synaptic events which may act as an inhibitory restraint, to protect against the spread of seizure-like activities 45 .…”
Section: Discussionmentioning
confidence: 94%
“…3b). The amplitude of stable PID (185±106 μV, 95% CI: , n=66 events from 8 slices) was significantly higher than that of simultaneous IID (49±24 μV, 95% CI: [42][43][44][45][46][47][48][49][50][51][52][53][54][55], n=66 events from 8 slices) (Wilcoxon test, Z(7)=3.99, P<0.01) (Fig. 3e) Fig.…”
Section: Pid Emerge During the Transition To The Ictal Statementioning
confidence: 99%
“…3 LVF and HYP seizures may mirror the activity of distinct limbic structures. 4 Accordingly, Velasco et al 2 have reported that LVF seizures rest on the activity of hippocampal and parahippocampal networks, whereas HYP seizures originate from local circuits in the hippocampal formation. In addition, TLE patients presenting with HYP seizures have histopathological patterns of atrophy that are consistent with hippocampal sclerosis, whereas LVF seizures are linked to a more diffuse and bilateral distribution of atrophy.…”
mentioning
confidence: 99%